High magnetic aspects of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline NiZn ferrite, Ni0.5Zn0.5Fe2O4, having particle size in the range 6-10 mn, has been synthesized by an auto-combustion method. The nanosized ferrite powder formed at a low temperature is annealed at different temperatures in the range 473-1273 K and characterized by X-ray diffraction, vibrating sample magnetometry, Mossbauer spectroscopy, transmission electron microscopy and scanning electron microscopy. Magnetic transition temperature broadening up to 773 K is observed for the nanosized sample, compared to the T-c = 563 K for the bulk material. Critical particle diameter (D-c) is found to be similar to 40 nm at which maximum coercivity is obtained for the powder sample annealed at 973 K. Similarly, high room temperature magnetization, comparable to that of the bulk material, is obtained for the powders annealed at 1073 K, with a maximum particle size of similar to 50 nm. Very little grain growth is observed for the powders annealed above 1073 K. The results show that, optimum magnetic properties can be achieved for fine particle NiZn ferrite powders synthesized by a low-temperature auto-combustion method and processed at relatively lower temperatures.